Study of Graphene-MoS2 Based SPR Biosensor with Graphene Based SPR Biosensor: Comparative Approach - Habib, Md Mortuza; Roy, Ruddro; Islam, Md Mojidul; Hassan, Mehedi; Islam, Md Muztahidul; Hossain, Md Biplob (International Journal of Natural Sciences Research, 2019)
In this paper, we compare the sensitivity of graphene-MoS2 based surface plasmon resonance (SPR) biosensor to graphene based SPR biosensor. Here, graphene is used as biomolecular recognition element (BRE) because of its high adsorption ability and optical characteristics which helps to improve sensor sensitivity, on the other hand MoS2 is used for it has larger band gap, high fluroscence quenching ability, higher optical absorption efficiency which improves further sensor sensitivity. In DNA hybridization event, numerically achieved results show that single layer of graphene-MoS2 based SPR biosensor is 175% more sensitive than single layer of graphene coated SPR biosensor. Surface plasmon resonance angle and spectrum of reflected power are numerically investigated for different concentrated complementary DNA strands. The variations of SPR angle is significantly computable for complementary DNA strands whereas these parameters are varied negligibly for mismatched DNA strands. Thus the proposed sensor effectively differentiates hybridization and single nucleotide polymorphisms (SNP) by examining the level of changes in SPR angle and reflected power spectrum.